Drinking settings and problems of intoxication. - Lang, E.; Stockwell, Tim; Rydon, P.; Lockwood, A. (1995)
A random household survey was used as a basis for exploring drinkers' reports regarding their alcohol consumption and experiences of alcohol-related harm at different drinking settings. Licensed drinking settings were chosen because previous research has shown that high risk drinking and resulting harm are more likely to occur there. A total of 321 drinkers who reported their recent heaviest drinking occasion took place on licensed premises were identified from a sample of 1160 adults in Perth, Western Australia. Univariate analyses showed that both high risk consumption and harmful outcomes were more probable for drinkers who were under 25, male, single and had not eaten, and who had been drinking at premises which were either hotels or nightclubs with a predominantly male clientele, where music was the main entertainment and where customers were dancing. Following logistic regression analyses it was found that premises where customers were dancing (and/or listening to music), were predominantly male, and where drunk customers were continued to be served, were significantly associated with high risk consumption. Logistic regression found that being under 25, male and drinking at premises where there was dancing and where drunk people continued to be served was a significant risk factor for alcohol-related harm. Taken together these findings support to the view that preventing alcohol-related harm will involve strategies which aim to reduce levels of consumption and intoxication on licensed premises.